(untitled) (CAHIERS MAGELLANES-NS, 2024)
Agro- based enterprises play a pivotal role in strengthening the economy of the India. Due to engagement of huge resources in the sector, its participation in the endeavour to embrace sustainability issues through its value creation process substantially effects the country’s pace towards approaching Sustainable Development Goals. This necessitates the comprehension of factors that influence the entrepreneurs of Agro based enterprises to adopt sustainable practices. The present study aims to establish understanding of such factors with the use of Garret Ranking Method. Undertaken in Jorhat district of Assam, the study revealed that as per the opinion of the entrepreneurs, Customer demand is the most significant factor leading to inclination of entrepreneurs towards sustainable practices.